RHOBTB2 Mutations Expand the Phenotypic Spectrum of Alternating Hemiplegia of Childhood. (16th March 2021) - Zagaglia, Sara; Steel, Dora; Krithika, S.; Hernandez-Hernandez, Laura; Custodio, Helena Martins; Gorman, Kathleen M.; Vezyroglou, Aikaterini; Møller, Rikke S.; King, Mary D.; Hammer, Trine Bjørg; Spaull, Robert; Fazeli, Walid; et al.
Abstract : Objective: To explore the phenotypic spectrum of RHOBTB2 -related disorders and specifically to determine whether patients fulfill criteria for alternating hemiplegia of childhood (AHC), we report the clinical features of 11 affected individuals. Methods: Individuals with RHOBTB2 -related disorders were identified through a movement disorder clinic at a specialist pediatric center, with additional cases identified through collaboration with other centers internationally. Clinical data were acquired through retrospective case-note review. Results: Eleven affected patients were identified. All had heterozygous missense variants involving exon 9 of RHOBTB2, confirmed as de novo in 9 cases. All had a complex motor phenotype, including at least 2 different kinds of movement disorder, e.g., ataxia and dystonia. Many patients demonstrated several features fulfilling the criteria for AHC: 10 patients had a movement disorder including paroxysmal elements, and 8 experienced hemiplegic episodes. In contrast to classic AHC, commonly caused by mutations in ATP1A3, these events were reported later only in RHOBTB2 mutation–positive patients from 20 months of age. Seven patients had epilepsy, but of these, 4 patients achieved seizure freedom. All patients had intellectual disability, usually moderate to severe. Other features include episodes of marked skin color change and gastrointestinal symptoms, each in 4 patients. Conclusion: Although heterozygous RHOBTB2 mutations were originally described in early infantile epileptic encephalopathy type 64, our study confirms that they account for a more expansive clinical phenotype, including a complex polymorphic movement disorder with paroxysmal elements resembling AHC. RHOBTB2 testing should therefore be considered in patients with an AHC-like phenotype, particularly those negative for ATPA1A3 mutations.